NMR Spectroscopic Analysis of the Local Structure of Porous-Type Amorphous Alumina Prepared by Anodization - Hashimoto, Hideki; Yazawa, Koji; Asoh, Hidetaka; Ono, Sachiko (Journal of physical chemistry. C, 2017)
Alumina is classified as an intermediate oxide that cannot form a glass and is industrially used as a multifunctional material. Intensive studies on the atomistic structure of amorphous alumina have been conducted because a fundamental understanding of its structure can be meaningful to the design of new materials and devices. Here we focused on anodic alumina as a model material for clarifying the atomistic structure of amorphous alumina and prepared anion-free and anion-incorporated porous-type amorphous alumina by anodization using chromic acid electrolyte and typical electrolytes (e.g., sulfuric acid, oxalic acid, and phosphoric acid), respectively. The local structure around aluminum atoms in the anodic alumina was investigated by nuclear magnetic resonance spectroscopy. We found that the structure of anodic amorphous alumina comprises AlO4, AlO5, and AlO6 units with predominant fractions of AlO5. We also observed that the fraction of each unit was 37.7, 54.3, and 8.0%, with an average coordination number (N Al–O) of 4.70 in the anion-free sample. The results of 1H–27Al cross-polarization with magic angle spinning measurements showed that the prevalence of AlO6 units decreased with the elimination of physisorbed water by heat treatment. We also suggest that the average N Al–O is affected by the depth, content, and/or species of incorporated anions and that the average N Al–O increases with increasing anion content in the case of samples prepared using sulfuric acid electrolyte. The results are quite meaningful because they provide precise information about the local structure of anodic amorphous alumina; previous reports on this subject have been inconsistent and controversial. We expect that the present results will accelerate structural analysis research on the atomistic structures of amorphous alumina.